2011
DOI: 10.4028/www.scientific.net/amr.287-290.1227
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Conduction of Anisotropic Building Materials

Abstract: Heat conduction in anisotropic materials is quite different from that in isotropic materials. Heat flux vector is commonly not perpendicular to the isothermal surface in anisotropic materials. The advantage and disadvantage of anisotropic materials were analyzed in this paper. The thermal conductivities at one point are not equal in all directions for anisotropic materials. The technique of double skin facade has been successfully applied in many building designs. The application of combining building envelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In winter, it would be advantageous in terms of thermal comfort to close the openings since external temperature is always lower than inside the building. Existing studies and cases have shown that, as mentioned in the introduction, the static air buffer is the optimal type in winter because it acts as a thermal buffer [9][10][11][12][13][14][15]38] (Figure 3a). …”
Section: Establishment Of An Airflow Operating Methods For a Dsfmentioning
confidence: 99%
See 2 more Smart Citations
“…In winter, it would be advantageous in terms of thermal comfort to close the openings since external temperature is always lower than inside the building. Existing studies and cases have shown that, as mentioned in the introduction, the static air buffer is the optimal type in winter because it acts as a thermal buffer [9][10][11][12][13][14][15]38] (Figure 3a). …”
Section: Establishment Of An Airflow Operating Methods For a Dsfmentioning
confidence: 99%
“…In winter, the heat in the cavity can considerably reduce the heating load of a building in terms of thermal comfort. Particularly, in winter, conducting the heat in the cavity to the building's interior can be maximized by using a static air buffer as an airflow operating method, which seals the heat in the cavity [9][10][11][12]. The Telus Headquarters building in Toronto and the Occidental Chemical buildings in Niagara Falls and in New York use a static air buffer as an airflow operating method to reduce heating energy consumption in winter [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation